Molecular Mechanisms and Potential Clinical Applications of Campylobacter jejuni Cytolethal Distending Toxin - Lai, Cheng-Kuo; Chen, Yu-An; Lin, Chun-Jung; Lin, Hwai-Jeng; Kao, Min-Chuan; Huang, Mei-Zi; Lin, Yu-Hsin; Chiang-Ni, Chuan; Chen, Chih-Jung; Lo, U-Ging; Lin, Li-Chiung; Lin, Ho; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Cytolethal distending toxin (CDT), a genotoxin produced by Campylobacter jejuni, is composed of three subunits: CdtA, CdtB, and CdtC. CdtB is a DNase that causes DNA double-strand breaks (DSB) in the nucleus resulting in cell cycle arrest at the G2/M stage and apoptosis. CdtA and CdtC bind to cholesterol-rich microdomains on the cytoplasmic membrane, a process required for the delivery of CdtB to cells. Although a unique motif associated with cholesterol-binding activity has been identified in other pathogens, the mechanism underlying the interaction between the CdtA and CdtC subunits and membrane cholesterol remains unclear. Also, the processes of cell uptake and delivery of CdtB in host cells and the translocation of CdtB into the nucleus are only partially understood. In this review, we focus on the underlying relationship among CDT, membrane cholesterol, and the intracellular trafficking pathway as a unique mechanism for C. jejuni-induced pathogenesis. Moreover, we discuss the clinical aspects of a possible therapeutic application of CDT in cancer therapy. Understanding the molecular mechanism of CDT-host interactions may provide insights into novel strategies to control C. jejuni infection and the development of potential clinical applications of CDT.